1993
DOI: 10.1002/hep.1840180104
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of hepatitis C virus by competitive reverse transcription—polymerase chain reaction: Increase of the virus in advanced liver disease

Abstract: We developed a quantitative method of hepatitis C virus RNA by competitive reverse transcription-polymerase chain reaction. With this method, 36 patients with type C chronic liver disease were analyzed for the copy number of circulating hepatitis C virus in 50 microliters of serum. The amounts of hepatitis C virus RNA ranged from 10(1) to 10(7) copies in the 36 patients. The average amount of hepatitis C virus RNA was 10(3.3 +/- 2.2) copies in 12 patients with chronic persistent hepatitis, 10(5.7 +/- 1.6) copi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
96
0

Year Published

1995
1995
2007
2007

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 180 publications
(101 citation statements)
references
References 17 publications
5
96
0
Order By: Relevance
“…Some investigators have shown that viral load increased in proportion to the length of HCV infection, suggesting that this fact might be a cause of progression of HCV-induced chronic liver disease. 28 However, liver histology data of our post-transfusional patients showed a more severe liver damage in adults than in children, both with a similar duration of HCV infection,…”
Section: Discussionmentioning
confidence: 56%
“…Some investigators have shown that viral load increased in proportion to the length of HCV infection, suggesting that this fact might be a cause of progression of HCV-induced chronic liver disease. 28 However, liver histology data of our post-transfusional patients showed a more severe liver damage in adults than in children, both with a similar duration of HCV infection,…”
Section: Discussionmentioning
confidence: 56%
“…Many previous studies have examined the significance of both parameters independently. The wide range of clinicopathological correlations between serum and intrahepatic RNA levels (20,23,24,31,32,35,38,42,47,50,51), together with discrepancies in the literature among authors who find correlation between quasispecies complexity and liver damage (25,28,33,61) and those who do not (22,36,48,56), suggests that the relation between viral load and liver injury is more complex than expected.Recently, we have proven that, within an infected patient, the composition of the circulating viral population does not necessarily reflect the composition of the hepatic population (5), although the causes for this difference remain obscure. Heterogeneous quasispecies in peripheral blood mononuclear cells (PBMC) of humans and in chimpanzees have been described (34, 37, 49, 54, 57), and it has been proposed that replication in this tissue might contribute to HCV serum quasispecies complexity.…”
mentioning
confidence: 99%
“…To quantify a very small copy number of the viral RNA, it was essential to develop a quantitative and competitive polymerase chain reaction (QCPCR) assay as used for titration of human immunodeficiency virus (Kato et al, 1993;Piatak et al, 1993). The strategy of the QCPCR for titration of HCV RNA is described in Fig.…”
mentioning
confidence: 99%